Developing agricultural knowledge and skills by using a learning kit on commercial native chicken rearing of agricultural teacher apprentice students, Surindra Rajabhat University - Thongsuk, P.; Poungsuk, P.; Junlex, P. (My University, 2023)
According to the comprehensive development of agricultural knowledge and skills of the agricultural teacher apprentice students, it was developed as a new agricultural learning kit which was consistent with learning era in the 21st century and the digital age. Results was showb to be 3 parts. Firstly, five components gained from the learning kid development as building a chicken house and appropriate equipment preparation, management of native chicken rearing, management of waste utilization, processing and distribution management and preparing online media for learning. The learning kid assessment showed very high level (x =4.36; S.D.=0.165). Secondly, four mouths resulted of 100 native chicken rearing that caged chicken rearing gave higher survival rate than free-range rearing with a statistical significance level at P=0.05. However, there was not statistical significantly differed at P=0.05 in terms of food cost, food intake, weight gain, food conversation ratio, return per head, net profit per head, the return on weight gain, production loss index, and production efficiency throughout the experiment. Thirdly, development of agricultural knowledge and skills increased in learning achievement at a significance level at P=0.01. As a whole, the assessment of native chicken rearing was found at a high level (x =4.43; S.D.=0.178). Based on results, the management of native chicken rearing was found at highest level (x =4.68 S.D.=0.125) and followed by skills in processing and distribution (x =4.35 S.D.=0.136) and online media preparing (x =4.23 S.D.=0.142). The confidence in the adoption of knowledge and skills in teaching native chicken rearing were found at highest level (x =4.58 S.D.=0.185). It is suggested that a mixed farming learning kit and a learning kit through online systems should be developed for a highest efficiency.
Keywords: Agricultural knowledge and skills; Caged chicken rearing; Free-range chicken rearing; Learning achievement; Native chicken rearing